Legal Russian in Legal - Linguistic Research - GALDIA, Marcus (Comparative Legilinguistics, 2017)
The article focuses upon the emergence and the development of the legal Russian language and the methodology used for its scrutiny in the legal-linguistic research in Russia and abroad. It shows some of the dominant tendencies in the legal-linguistic and related research in a perspective that combines material issues concerning the work on textual sources and their identification as well as methods developed in Russia to deal with legal- linguistic problems. The author aims to portray methodological continuity and discontinuity in a research area with a relatively long history. The overview of topics and methods demonstrates that the development in the area of the legal-linguistic research in Russia displays all characteristic features of the European legal-linguistic tradition, and especially the shift in the attention of scholars from isolated terminological issues to discursive aspects of law.